Analisis Keunggulan Komparatif Industri Pakan Ternak di Jawa Barat dan Lampung - Sumaryanto, nFN; Rusastra, I Wayan (Pusat Sosial Ekonomi dan Kebijakan Pertanian, 1991)
The role of feedmill industry in the livestock production system is very essential. Therefore the efficient feed production is required to support the poultry industry development. This study is intended to evaluate the economic feasibility of the feed industries in Lampung and West Java. The finding of this study indicated that poultry feed production is economically efficient under import substitution scenario, but on the border line under interregional trade regime, and is not feasible for export promotion. Although feedmill industries did not receive any input subsidies, they persistently enjoyed financial profit due to highly output price protection. The implication of the study is that the poultry feed production have to be vertically integrated with feedstuff supply and poultry production. Operationally the feedmills have to use local raw materials and the output (feed) should be directed to support livestock development in the respective region.